Candida Albicans Alcohol Dehydrogenase 1 gene in oral dysplasia and oral squamous cell carcinoma - Hafed, Layla; Farag, Heba; El-Rouby, Dalia; Shaker, Olfat; Shabaan, Hebat-Allah (Polish Journal of Pathology, 2019)
This study was designed to examine the prevalence of Candida albicans alcohol dehydrogenase 1 (CaADH1) gene in oral dysplasia as well as oral squamous cell carcinoma (OSCC) with and without lymph node metastasis (LNM) using reverse transcription polymerase chain reaction (RT-PCR) in order to determine its role in initiation, propagation and metastasis of oral dysplasia and carcinoma. Formalin-fixed parafin-embedded specimens were grouped into four groups: 7 control, 16 oral dysplasia, 16 OSCC without LNM and 15 OSCC with LNM. All specimens were examined by periodic acid Schiff (PAS) stain to detect Candida hyphae, while CaADH1 gene was detected using RT-PCR. Candida hyphae were detected by PAS stain in one specimen of oral dysplasia group, 5 OSCC without LNM and 5 OSCC with LNM. CaADH1 gene was detected in 29 specimens (one case of sever dysplasia, 16 OSCC without LNM and 12 OSCC with LNM), with a highly statistically significant between the groups. CaADH1 gene is associated with OSCC with and without metastasis whereas in oral dysplasia it could not be estimated. Further studies with larger sample size are needed to confirm the role of CaADH1 in oral dysplasia and OSCC.